Obligation to Adjust the Foundation Budget According to Law Number 28 Year 2004 Concerning Amendment to Law Number 16 Year 2001 Regarding Foundations - PL Tobing; Dwi Cahyono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Foundations are considered as the answer for those who want a forum or institution that can channel their desire to carry out all activities that basically aim to do good deeds, so that their actions are voluntary actions (tabarru) to give wealth. Although the Foundation has been recognized as a legal entity, the Foundation as a legal entity is different from a limited liability company, especially in terms of purpose. The purpose of the Foundation is social and ideal, but there is no law that prohibits the Foundation from running a company. There are Foundation business activities that are carried out not at the time of making profit, such as Foundations that run Polyclinics or Hospitals, or schools (educational institutions). PP Number 2 of 2013 was issued by the government with the aim of reviving foundations that have been deemed to have lost their legal entity status in accordance with the provisions stipulated in Law Number 16 of 2991 concerning Foundations as amended by Law Number 28 of 2004. The formulation of the problem to be addressed The authors discuss are: 1) How is the existence of foundations that have not implemented adjustments to their articles of association with Law Number 28 of 2004 concerning Amendments to Law Number 16 of 2001 concerning Foundations? and 2) What are the legal consequences for foundations that have not adjusted their articles of association with Law Number 28 of 2004 concerning Amendments to Law Number 16 of 2001 concerning Foundations. The research method that the author uses is a descriptive normative juridical method where in normative research it is conceptualized as something written in laws and regulations or laws that are conceptualized as rules or norms that are benchmarks for community behavior towards what is considered appropriate. Finally, based on the results of the research, the authors concluded that with the enactment of Law Number 28 of 2004, existing foundations are regulated in the Transitional Regulation Article 71 of the Foundation Law which stipulates that foundations that existed before the foundation law adjusts their articles of association. Replace according to the writing above within the stipulated time, namely with the provisions, for foundations that existed before the enactment of the law on foundations, the foundation was required to remain recognized as a legal entity. For those who do not meet the requirements as referred to in point 1 a (not recognized as a legal entity), can obtain legal entity status by adjusting the articles of association according to the above and submitting an application to the Minister within 1 (one) year from the enactment of the foundation law.